Assessing the environmental impacts of healthier diets. Final report to Defra on project FO0427 - Williams, Adrian; Morris, Joe; Audsley, Eric; Hess, Tim M.; Goglio, Pietro; Burgess, Paul J.; Chatterton, Julia; Pearn, Kerry; Mena, Carlos; Whitehead, Peter (Cranfield University, 2018)
Summary: oncern about the public health impacts of dietary habits in the UK have led to initiatives to encourage healthier eating, notably in the dietary guidelines represented of the eatwell plate (FSA, 2007) and the Eatwell Guide (NHS, 2016c). A change in UK dietary habits towards healthier eating would result in changes in the type and quantities of food items in the national diet, with implications for agricultural, food and allied industries. More specifically, this could lead to changes in land use and farming practices, both for the UK and its trading partners, with associated effects on greenhouse gas emissions and other environmental impacts. In this context, and sponsored by Defra, this study set out using a series of scenarios to assess the environmental impacts of changing dietary habits and specifically the adoption of healthier eating in the UK, and in broad terms some of the likely social and economic impacts on the agricultural and food sector, through a set of hypothetical scenarios. The main objectives were to: i) determine the consumption of food under possible future food consumption scenarios in the UK, including the eatwell plate; ii) quantify the production of agricultural commodities needed to meet the food needs of each scenario; iii) quantify the environmental impacts of food commodity production and consumption by scenarios, and iv) identify, in broad terms, the possible economic and societal impacts of dietary changes.